Growth Indices of Low and Normal Birth Weight of 2-5 year Old Children in Rural Areas of Gonbad , Iran - Abdol-Hamed Yapan-Gharavi; Behrooz Ebrahimzadehkor; Ata-Mohammad Dorri (Journal of Research Development in Nursing and Midwifery, 2015)
Background and Objective: Given the correlation of birth weight with growth indices, this study aimed at determing the growth indices of low birth weight (LBW) and normal birth weight of 2-5 year old children in rural areas of Gonbad, Iran.